PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN MODEL STUDENT TEAMS ACHIEVEMENT DIVISIONS BERBANTUAN WORDWALL DI KELAS IV SDN 16 NAN BALIMO KOTA SOLOK - Aulia Putri, Indah; Amsari, Dina; Meizatri, Ranti; Bungsu Ladiva, Hasmai (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
As a result of teacher-centered instructional practices, low student engagement and collaboration, and the ineffective implementation of assessment and group learning activities, this study was undertaken in response to the low learning outcomes of fourth-grade students in Pancasila Education. Because of these problems, the Daily Assessment results showed that an average score of 66.34 was achieved by the students, with 10 out of 26 students meeting the Minimum Learning Achievement Criteria (75). The other 16 students did not meet the required norm. Also, numerous parts of the Deep Learning Lesson Plan (Rencana Pembelajaran Mendalam/RPM) did not meet the necessary standards when we evaluated it. This research aimed to investigate how the Student Teams Achievement Divisions (STAD) learning paradigm, which is supported by Wordwall, improved the learning results of Pancasila Education students in Grade IV at SDN 16 Nan Balimo, Solok City. This study used a mixed-methods approach based on the principles of Classroom Action Research. There were a total of two sessions that made up Cycle I of the study, and a single meeting that made up Cycle II. A total of 26 fourth graders and one classroom instructor took part. Assessments of learning outcomes, classroom observations, and lesson plans were among the methods used to collect data, along with both test and non-test approaches. The findings showed that using Wordwall to execute the STAD learning paradigm improved the learning process and the learning outcomes for the students. From Cycle I to Cycle II, the lesson plan quality increased from 89.28% to 96.42%. The percentage of learning activities used in class, by both instructors and students, also rose, from 78.57 percent to 92.8 percent. Cognitive accomplishment increased from 81.54 in Cycle I to 87.70 in Cycle II, and 84.61% of students demonstrated mastery of classical learning. Also, results for affective learning was up from 62.9% to 78.6%, while results for psychomotor learning went up from 67.5% to 83.3%. These results suggest that fourth graders in Pancasila Education benefited greatly from the STAD learning approach, which was made possible via Wordwall.